2011
DOI: 10.1007/s11262-011-0572-1
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of NS5B gene of classical swine fever virus isolates indicates plausible Chinese origin of Indian subgroup 2.2 viruses

Abstract: Twenty-three CSFV isolates recovered from field outbreaks in various parts of India during 2006-2009 were used for genetic analysis in the NS5B region (409 nts). Seventeen of these were studied earlier [16] in the 5'UTR region. Phylogenetic analysis indicated the continued dominance of subgroup 1.1 strains in the country. Detailed analysis of a subgroup 2.2 virus indicated the plausible Chinese origin of this subgroup in India and provided indirect evidence of routes of CSFV movement within South East Asia reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 28 publications
2
27
0
Order By: Relevance
“…Present and previous studies of genetic typing [15] in Karnataka had indicated that there has been a switch in virus populations from subgroup 1.1 to 2.2 after 2008 and 2.2 viruses has dominated the field infections. Even though subgroup 1.1 viruses were predominant in India, the subgroup 2.2 viruses are gradually spreading as confirmed by frequent detection/ isolation of subgroup 2.2 viruses in the recent years, particularly from the northern India [14,15] and neighbouring country like Nepal [18]. During 2012-13, the prevalence of subgroup 2.2 isolates was also reported from Andhra Pradesh, Punjab, Orissa, Meghalaya and Arunachal Pradesh states (Unpublished data from NIVEDI, Bangalore).…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Present and previous studies of genetic typing [15] in Karnataka had indicated that there has been a switch in virus populations from subgroup 1.1 to 2.2 after 2008 and 2.2 viruses has dominated the field infections. Even though subgroup 1.1 viruses were predominant in India, the subgroup 2.2 viruses are gradually spreading as confirmed by frequent detection/ isolation of subgroup 2.2 viruses in the recent years, particularly from the northern India [14,15] and neighbouring country like Nepal [18]. During 2012-13, the prevalence of subgroup 2.2 isolates was also reported from Andhra Pradesh, Punjab, Orissa, Meghalaya and Arunachal Pradesh states (Unpublished data from NIVEDI, Bangalore).…”
Section: Discussionmentioning
confidence: 92%
“…In China, 94 % of the virus strains isolated from field outbreaks during 1986-1999 were belonging to 2.1 and 2.2 subgroups [27].As the present isolates and some of the Indian isolates belonged to subgroup 2.2, it can be inferred that the viruses may have had Chinese origin at some point of time. Recently, Patil et al [15] have also shown the plausible Chinese origin of the Karnataka isolate IND-294/08 which belongs to subgroup 2.2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations